2020
DOI: 10.3390/foods9070932
|View full text |Cite
|
Sign up to set email alerts
|

Health Promoting Bioactive Properties of Novel Hairless Canary Seed Flour after In Vitro Gastrointestinal Digestion

Abstract: The bioactive properties and health-promoting effects of two novel yellow (C09052, C05041) and two brown (Calvi, Bastia) hairless canary seed (Phalaris canariensis L.) cultivars were investigated in comparison to two common cereal grains (wheat and oat). The cereal flours were digested using the standardized INFOGEST in vitro human gastrointestinal digestion model. The three-kilo dalton molecular weight cutoff (3 kDa MWCO) permeate of the generated digestates was assessed in vitro for their antioxidant, chelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…Several studies have reported that HCS groats hold great potential as a wholegrain food ingredient and/or sustainable source of starch, protein, and oil [13,15,16]. HCS is also considered a health food ingredient being a good source of bioactive peptides, carotenoids, and phenolic compounds [13,17,18]. Currently, little or no data are available on carotenoid composition in HCS and the effect of processing on carotenoids in the end products.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that HCS groats hold great potential as a wholegrain food ingredient and/or sustainable source of starch, protein, and oil [13,15,16]. HCS is also considered a health food ingredient being a good source of bioactive peptides, carotenoids, and phenolic compounds [13,17,18]. Currently, little or no data are available on carotenoid composition in HCS and the effect of processing on carotenoids in the end products.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid composition of the CSPF is shown in Table 1. In particular, the CSPF had a higher content of glutamic acid 30.7%, isoleucine 4.3%, and histidine 2.0% compared to raw unhydrolyzed canary seed protein containing 26.0, 3.9, and 1.6%, respectively [5]. Concerning other cereal proteins, glutamic acid in the CSPF was also higher than that of rice (19%), maize (18%), barley (23%), oat (21%), and rye (24%) [1,32].…”
Section: Proximal Composition and Amino Acid Analysismentioning
confidence: 94%
“…Hairless canary seed (Phalaris canariensis L.) is a novel cereal grain that has gained the attention of scientists due to its high protein content (23%), unique starch chemistry, and potential application as a functional ingredient [1][2][3][4]. Typical canary seeds are not safe for human consumption due to the presence of toxic siliceous hairs on the surface of the seeds' kernel; however, crossbreeding techniques allowed the development of novel hairless varieties that are safe and approved for human consumption [5]. Previous studies demonstrated the high in vitro antioxidant activity of canary seed extracts, and it was believed that phenolic compounds were responsible for their antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular weight distribution profile of the peptides present in the 3 kDa permeate of legume digestate was determined by size exclusion chromatography, following the procedure of Achouri et al [ 76 ] with modifications by Mason et al [ 77 ]. An Agilent-1200 Series HPLC system (Agilent Technologies Canada, Inc., Mississauga, ON, USA), equipped with a Enrich SEC-70 column (10 × 300 mm) (Bio-Rad Laboratories, Mississauga, ON, USA), was used.…”
Section: Methodsmentioning
confidence: 99%